Social construction of body image and Weight loss behaviour among overweight adolescents / Suriati Sidek - Sidek, Suriati (2016)
Obesity among adolescents is often associated with body image dissatisfaction. However, very few studies have examined body image, as a social construct, among overweight adolescents in Malaysia, and the process by which such construction is perceived, experienced and reacted to through various social interactions. The literatures also show that body dissatisfaction may lead to disordered eating behaviour, as a means to improve physical appearance. Therefore, this phenomenological study that was guided by the social constructionism lens, aims to explore the construct of body image and weight loss behaviour among overweight adolescents. Thirty-three in-depth semi-structured interviews with 13 to 17 years old male and female overweight adolescents from an urban setting in Selangor were analysed using thematic analysis. The present study found that body image is conceptualised through perceptual, affective, cognitive and behavioural domains of overweight adolescents. Overweight adolescents perceived body attributes as more important than other physical characteristics. They described their body image as it is based on the appearance comments and criticism that they received from social interactions with peers and parents. Most of them wanted to be thin for social acceptance. They believed that they may have difficulties in looking for a partner and susceptible to diseases based on their observation of other people and through available information from significant others and the media. They experienced weight-related teasing, peer rejection and negative stereotyping in daily encounters. These perceptions, beliefs, and personal experiences and observation may lead to body dissatisfaction. Although most participants are dissatisfied with their current body image, few however were having positive views of their bodies by highlighting the self-enhancement mechanisms. All overweight adolescents interviewed in this study, including those with a positive view of their body image wanted to reduce weight. These findings suggest that the link between body image and weight loss behaviour was the intention to lose weight. They believed they can reduce weight by dieting, participating in physical activities and consuming slimming products. However, skipping meal was the preferred weight loss behaviour and this finding suggests that overweight adolescents lack information related to healthy weight loss. Their preferences of weight loss behaviour are influenced by advices and feedbacks from significant others and sources of information from the media, and are limited by some of the barriers. This study has given a significant contribution to the current knowledge with respect to the methodological approach and the conceptual framework of body image and weight loss behaviour in the form of a newly developed framework. The proposed framework may explain the construct of body image and weight loss behaviour among adolescents in Malaysia.